Предмет: Химия,
автор: anmak132004
Fe-->Fe2O3-->Fe2(SO4)3-->Fe(OH)3→ Fe2O3->Fe(NO3)3-->Fe(OH)3
Ответы
Автор ответа:
1
Ответ:
4Fe+3O²=2Fe²O³
Fe²O³+3 H²SO⁴= Fe²(SO⁴)³+3 H²O
Fe²(SO⁴)³+6NaOH= 2Fe(OH)³+3 Na²SO⁴
2Fe(OH)³= Fe²O³+3H²O
Fe²O³+6HNO³= 2Fe(NO³)³+ 3H²O
Fe(NO³)³+3KOH= Fe(OH)³+3 KNO³
Похожие вопросы
Предмет: Русский язык,
автор: kolpakov1983alex
Предмет: Русский язык,
автор: romatikhonov
Предмет: Русский язык,
автор: валерия12шепеленко
Предмет: Химия,
автор: ysims
Предмет: Литература,
автор: донт51